The prevalence rate, mortality, and 5-year overall survival of Schistosoma japonicum patients with human malignancy - Liu, Xue-Fei; Ju, Shuai; Wang, Ke-Ying; Li, Ying; Qiang, Jin-Wei (Frontiers in Oncology, 2023)
Background Only a few studies have focused on the association between Schistosoma japonicum and human malignancy. The aim of this study was to update the prevalence rate, mortality, and 5-year overall survival of S. japonicum patients with human malignancy. Methods From January 20, 2018, to January 31, 2021, 5,866 inpatients were included in the study. A total of 656 S. japonicum patients with malignancy were identified. Cases were stratified by gender and age groups. The cancer sites, prevalence rate, mortality, and 5-year overall survival of the patients were reported. The S. japonicum patients with malignancy were further divided into a non-digestive system tumor group (n = 309) and a digestive system tumor group (n = 347), including those with cancer in the esophagus, stomach, colon, rectum, liver, gallbladder, bile duct, or pancreas. Chi-squared test and odds ratio with confidence intervals were performed between these two groups. Results Lung cancer was found the most common malignancy, accounting for 18.6% of all malignancies, followed by colorectal, stomach, liver, and gallbladder cancers. These five leading malignancies accounted for approximately 61.8% of all cases. Colorectal cancer was the leading cause of malignancy death, followed by lung, stomach, gallbladder, and liver cancers. These five leading causes of death accounted for approximately 55.6% of all death cases. Statistical significance was found in the prevalence rate between S. japonicum and non-S. japonicum patients with/without digestive system tumor (p < 0.001). The odds ratio of S. japonicum patients with digestive system tumors was 1.6 (95%CI: 1.4–1.9). Conclusion S. japonicum contributes to a significant prevalence and mortality in digestive system tumors, including colorectal, stomach, liver, and gallbladder cancers.